1982
DOI: 10.1021/bi00539a002
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics and kinetics of single residue replacements in avian ovomucoid third domains: effect on inhibitor interactions with serine proteinases

Abstract: Sequence determinations in our laboratory have yielded the primary structures of ovomucoid third domains from 35 avian species. From that list, 12 sequences could be arranged into a contiguous set such that each sequence differs from a second by a single amino acid replacement. For this set of domains and for five additional domains of special interest, we report here the association equilibrium constants for their binding with bovine alpha-chymotrypsin, elastase I, and subtilisin Carlsberg. The results are in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
113
0
1

Year Published

1985
1985
2001
2001

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 181 publications
(119 citation statements)
references
References 44 publications
4
113
0
1
Order By: Relevance
“…Interestingly, using volumes to obtain ASP values (cal/A3) produces the best correlation, suggesting that cavity formation is an important parameter in calculating the free The experimental association energies were obtained from the literature. a, Vincent and Lazdunski (1972); b, Vincent et al (1974); c, Chen and Bode (1983); d, Hass and Ryan (1980); e, Bunting and Myers (1975); f, Read et al (1983); g, Ascenzi et al (1988); h, Empie and Laskowski (1982); i, Bode (1979) and Bolognes et al (1982); j , Pekar and Frank (1972); k , Akasaka et al (1982); I, Sheriff et al (1987); m, Ross et al (1977). Chothia and Janin (1975) first suggested that the free energy of association was related to the amount of surface area that was buried in the interface.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, using volumes to obtain ASP values (cal/A3) produces the best correlation, suggesting that cavity formation is an important parameter in calculating the free The experimental association energies were obtained from the literature. a, Vincent and Lazdunski (1972); b, Vincent et al (1974); c, Chen and Bode (1983); d, Hass and Ryan (1980); e, Bunting and Myers (1975); f, Read et al (1983); g, Ascenzi et al (1988); h, Empie and Laskowski (1982); i, Bode (1979) and Bolognes et al (1982); j , Pekar and Frank (1972); k , Akasaka et al (1982); I, Sheriff et al (1987); m, Ross et al (1977). Chothia and Janin (1975) first suggested that the free energy of association was related to the amount of surface area that was buried in the interface.…”
Section: Resultsmentioning
confidence: 99%
“…A hallmark of the lock-and-key mode of complex stabilization is the destabilizing effect of amino acid substitutions in reactive center loop residues of such inhibitors on complex formation, as reflected by increases in the rate constants for complex dissociation (47). Our finding that reactive center loop mutations in antithrombin minimally affect the rate constants for dissociation of antithrombin-proteinase complexes thus supports the idea that reactive center loop interactions with the proteinase active site do not significantly contribute to stabilizing the complexes.…”
Section: Discussionmentioning
confidence: 99%
“…The P3 to P2' residues run as follows: Cys-16, Thr-17, Met-18, Glu-19, Tyr-20. Thus, in contrast to OMJPQ3, which is a trypsin inhibitor because of a lysine residue at its PI position, the methionine of OMSVP3 determines its preferred inhibitory specificity towards chymotrypsin, elastase and subtilisin [7]. OMTKY3 differs from OMSVP3 only by a leucine residue in the PI position resulting in almost identical binding constants.…”
mentioning
confidence: 99%